Research Theory and Progress of Downstream Response to Imposed Flow Transformation - HOU Jun; ZHANG Yue; AO Yanhui; MIAO Lingzhan; WU Jun (Renmin Zhujiang)
This study aims to explore the research progress and development direction of environmental flow and supplement the research methods regarding environmental flow assessment.Specifically,the research progress of environmental flow in and outside China is summarized.Then,the software CiteSpace is used to analyze the historical hotspots and research topic evolution of research methods for environmental flow since the 21st century on the basis of the CNKI and Web of Science databases.Next,a holistic method for environmental flow assessment,namely,downstream response to imposed flow transformation (DRIFT),is introduced in detail from the aspects of development background,model modules,and application steps.Finally,the application of this method in environmental flow assessment and ecosystem protection is summarized given the cases of the Okavango and Zambezi River projects in South Africa.The results provide a new idea and method for the study of environmental flow.